Does MIS Surgery Allow for Shorter Constructs in the Surgical Treatment of Adult Spinal Deformity?. Issue 3 (3rd February 2017) - Uribe, Juan S.; Beckman, Joshua; Mummaneni, Praveen V.; Okonkwo, David; Nunley, Pierce; Wang, Michael Y.; Jr, Gregory M. Mundis; Park, Paul; Eastlack, Robert; Anand, Neel; Kanter, Adam; Lamarca, Frank; et al.
Abstract: BACKGROUND: The length of construct can potentially influence perioperative risks in adult spinal deformity (ASD) surgery. A head-to-head comparison between open and minimally invasive surgery (MIS) techniques for treatment of ASD has yet to be performed. OBJECTIVE: To examine the impact of MIS approaches on construct length and clinical outcomes in comparison to traditional open approaches when treating similar ASD profiles. METHODS: Two multicenter databases for ASD, 1 involving MIS procedures and the other open procedures, were propensity matched for clinical and radiographic parameters in this observational study. Inclusion criteria were ASD and minimum 2-year follow-up. Independent t -test and chi-square test were used to evaluate and compare outcomes. RESULTS: A total of 1215 patients were identified, with 84 patients matched in each group. Statistical significance was found for mean levels fused (4.8 for circumferential MIS [cMIS] and 10.1 for open), mean interbody fusion levels (3.6 cMIS and 2.4 open), blood loss (estimated blood loss 488 mL cMIS and 1762 mL open), and hospital length of stay (6.7 days cMIS and 9.7 days open). There was no significant difference in preoperative radiographic parameters or postoperative clinical outcomes (Owestry Disability Index and visual analog scale) between groups. There was a significant difference in postoperative lumbar lordosis (43.3° cMIS and 49.8° open) and pelvic incidence-lumbar lordosis correction (10.6° cMIS and 5.2° open) in the open group. There was no significant difference in reoperation rate between the 2 groups. CONCLUSION: MIS techniques for ASD may reduce construct length, reoperation rates, blood loss, and length of stay without affecting clinical and radiographic outcomes when compared to a similar group of patients treated with open techniques.